Design for wellbeing : an applied approach - Petermans, Ann; Cain, Rebecca, 1978- (Design for social responsibility series, 2020)
"Design for Wellbeing charts the development and application of design research to improve the personal and societal wellbeing and happiness of people. It draws together contributions from internationally leading academics and designers to demonstrate the latest thinking and research on the design of products, technologies, environments, services and experiences for wellbeing. Part 1 starts by conceptualizing wellbeing and takes an in-depth look at the rise of the design for wellbeing movement. Part 2 then goes on to demonstrate design for wellbeing in practice through a broad range of domains from products, environments and services. Among others, we see emerging trends in the design of interiors and urban spaces to support wellbeing, designing to enable and support connectedness and social interaction, and designing for behavior change to tackle unhealthy eating behavior in children. Significantly, the body of work on subjective wellbeing - design for happiness, is increasing, and several case studies are provided on this so as to demonstrate how design can contribute to support the wellbeing of people. Part 3 provides practical guidance for designing for wellbeing through a range of examples of tools, methods and approaches, which are highly user-centric, participatory and critical and speculative. Finally the book concludes in Part 4 with a look to future challenges for design for wellbeing. The book will provide students, researchers and practitioners a detailed assessment of design for wellbeing, taking a distinctive global approach to design practice and theory in context. Design for Wellbeing concerns designers and organizations but also defines its broader contribution to society, culture and economy"--